Design of a Guest Face Detection Tool Using ESP32-CAM Based on Internet of Things (IoT) - Khadafi, Muhamad; Pardede, A M H; Sembiring, Hermansyah (Yayasan Kita Menulis, 2024)
This research develops an Internet of Things (IoT)-based guest face detection tool using ESP32-CAM to create a digital guestbook archive. The device distinguishes between guests and employees, with employee face data stored in a GitHub repository. When the device detects an unfamiliar guest face, a notification and photo are sent to a Telegram bot. If an employee's face is detected, a notification of the employee's name is sent to the Telegram bot. The method used is prototyping and the test results show that this tool is effective in detecting and digitally archiving guest visits.